2011
DOI: 10.1111/j.1462-2920.2011.02499.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic diguanylate turnover mediated by the sole GGDEF/EAL response regulator in Pseudomonas putida: its role in the rhizosphere and an analysis of its target processes

Abstract: GGDEF and EAL/HD-GYP protein domains are responsible for the synthesis and hydrolysis of the bacterial secondary messenger cyclic diguanylate (c-di-GMP) through their diguanylate cyclase and phosphodiesterase activities, respectively. Forty-three genes in Pseudomonas putida KT2440 are putatively involved in the turnover of c-di-GMP. Of them only rup4959 (locus PP4959) encodes a GGDEF/EAL response regulator, which was identified in a genome wide analysis as preferentially induced while this bacterium colonizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
105
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 100 publications
6
105
0
Order By: Relevance
“…In particular, the stress sigma factor RpoS positively or negatively regulated 15 of the 21 genes upon entry into the stationary phase. Regulation of the GGDEF/EAL domain-encoding genes by RpoS has also been observed in other bacteria (325,364) and seems to represent a common trait. While six of the RpoS-controlled genes regulate CsgD and curli gene expression, downstream targets of most of the other GGDEF/EAL domain-encoding genes remain to be determined.…”
Section: Gmp Signaling Pathwaysmentioning
confidence: 93%
“…In particular, the stress sigma factor RpoS positively or negatively regulated 15 of the 21 genes upon entry into the stationary phase. Regulation of the GGDEF/EAL domain-encoding genes by RpoS has also been observed in other bacteria (325,364) and seems to represent a common trait. While six of the RpoS-controlled genes regulate CsgD and curli gene expression, downstream targets of most of the other GGDEF/EAL domain-encoding genes remain to be determined.…”
Section: Gmp Signaling Pathwaysmentioning
confidence: 93%
“…No detectable differences were observed in planktonic growth of the strains. Cultures harboring pMAMV1 were vortexed in the presence of glass beads (diameter, 0.5 mm) to disrupt aggregates that appeared as a consequence of high levels of c-di-GMP (31). Experiments were repeated at least three times with two technical repeats per sample, and data are given in Miller units.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmids pMMG1 (P lapF ::lacZ), pMMG2 (P lapF ::gfp), pMMGA (P lapA :: lacZ), pMAMV21 harboring an rpoS::lacZ translational fusion, and pMAMV1 carrying the diguanylate cyclase-encoding gene rup4959 have been described elsewhere (22,31,32). E. coli was grown at 37°C in LB medium (33).…”
Section: Methodsmentioning
confidence: 99%
“…Since the switch of bacterial lifestyle from planktonic to sessile growth requires alterations in bacterial physiology, the expression of a large number of genes is changed during the process of colonization (Mathesius, 2009;Matilla et al, 2007Matilla et al, , 2011Ramos-González et al, 2005). Matilla et al (2007) identified 93 P. putida genes from 11 functional classes which exhibited increased expression when the bacteria grew in the maize rhizosphere, including genes for motility, such as fliL and fliB, and several transcriptional regulators.…”
Section: Introductionmentioning
confidence: 99%